Electrolyte and plasma responses after pickle juice, mustard, and deionized water ingestion in dehydrated humans - Miller, K. C. (Journal of Athletic Training, 2014)
Context: Some athletes ingest pickle juice (PJ) or mustard to treat exercise-associated muscle cramps (EAMCs). Clinicians warn against this because they are concerned it will exacerbate exercise-induced hypertonicity or cause hyperkalemia. Few researchers have examined plasma responses after PJ or mustard ingestion in dehydrated, exercised individuals.